Monitoring of carbon monoxide in residences with bulk wood pellet storage in the Northeast United States. (3rd October 2017) - Rossner, Alan; Jordan, Carolyn E.; Wake, Cameron; Soto-Garcia, Lydia
ABSTRACT: The interest in biomass fuel is continuing to expand globally and in the northeastern United States as wood pellets are becoming a primary source of fuel for residential and small commercial systems. Wood pellets for boilers are often stored in basement storage rooms or large bag-type containers. Due to the enclosed nature of these storage areas, the atmosphere may exhibit increased levels of carbon monoxide. Serious accidents in Europe have been reported over the last decade in which high concentrations of carbon monoxide (CO) have been found in or near bulk pellet storage containers. The aim of this study was to characterize the CO concentrations in areas with indoor storage of bulk wood pellets. Data was obtained over approximately 7 months (December 2013 to June 2014) at 25 sites in New Hampshire and Massachusetts: 16 homes using wood pellet boilers with indoor pellet storage containers greater than or equal to 3 ton capacity; 4 homes with wood pellet heating systems with outdoor pellet storage; 4 homes using other heating fuels; and a university laboratory site. CO monitors were set up in homes to collect concentrations of CO in the immediate vicinity of wood pellet storage containers, and data were then compared to those of homes using fossil fuel systems. The homes monitored in this study provided a diverse set of housing stock spanning two and a half centuries of construction, with homes built from 1774 to 2013, representing a range of air exchange rates. The CO concentration data from each home was averaged hourly and then compared to a threshold of 9 ppm. While concentrations of CO were generally low for the homes studied, the need to properly design storage locations for pellets is and will remain a necessary component of wood pellet heating systems to minimize the risk of CO exposure. Implications : This paper is an assessment of carbon monoxide (CO) exposure from bulk wood pellet storage in homes in New Hampshire and Massachusetts. Understanding the CO concentrations in homes allows for better designs for storage bins and ventilation for storage areas. Hence, uniform policies for stored wood pellets in homes, schools, and businesses can be framed to ensure occupant safety. Currently in New York State rebates for the installation of wood pellet boilers are only provided if the bulk pellet storage is outside of the home, yet states such as New Hampshire, Vermont, and Maine currently do not have these restrictions.